Improved Bioavailability and High Photostability of Methotrexate by Spray-Dried Surface-Attached Solid Dispersion with an Aqueous Medium - Bhupendra Raj Giri; Jung Suk Kim; Jong Hyuck Park; Sung Giu Jin; Kyeong Soo Kim; Fakhar ud Din; Han Gon Choi; Dong Wuk Kim (MDPI AG, 2021)
Low aqueous solubility and poor bioavailability are major concerns in the development of oral solid-dosage drug forms. In this study, we fabricated surface-attached solid dispersion (SASD) to enhance the solubility, bioavailability, and photostability of methotrexate (MTX), a highly lipophilic and photo-unstable drug. Several MTX-loaded SASD formulations were developed for spray-drying using water as the solvent, and were investigated for their aqueous solubility and dissolution kinetics. An optimized ternary SASD formulation composed of MTX/ sodium carboxymethyl cellulose (Na-CMC)/sodium lauryl sulfate (SLS) at 3/0.5/0.5 (w/w) had 31.78-fold and 1.88-fold higher solubility and dissolution, respectively, than MTX powder. For SASD, the in vivo pharmacokinetic parameters AUC and Cmax were 2.90- and 3.41-fold higher, respectively, than for the MTX powder. Solid-state characterizations by differential scanning calorimetry and X-ray diffraction revealed that MTX exists in its crystalline state within the spray-dried SASD. The MTX-loaded SASD formulation showed few physical changes with photostability testing. Overall, the results indicate that the spray-dried MTX-loaded SASD formulation without organic solvents enhances the solubility and oral bioavailability of MTX without a significant deterioration of its photochemical stability.